2013
DOI: 10.1002/bsl.2072
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Violent Predators: Toward Reasonable Estimates of Recidivism Base Rates

Abstract: The sexual recidivism rate of sex offenders is a controversial issue. Perhaps as controversial is the sexual recidivism rate of the select group of sex offenders who are examined pursuant to sexually violent predator (SVP) statutes. At present, reliable estimates of SVP recidivism are unavailable. We propose that reasonable estimates of SVP recidivism can be reached by considering three available pieces of data: (i) a likely recidivism rate of the general population of sex offenders; (ii) procedures typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Even though evidence suggests that evaluators are quite adept at selecting only the highest risk offenders for civil commitment (Levenson, 2004 ;Mercado, Jeglic, Markus, Hanson, & Levenson, 2013 ), risk level alone is not suffi cient to identify those who ultimately will or will not recidivate. Overall, between 10 and 40 % of civilly committed SVPs can be expected to commit further sex offenses should they be released (Duwe, 2014 ;Milloy, 2003 ;Neller & Petris, 2013 ). While higher than the average rate of recidivism among non-SVP sex offenders (Hanson & Bussiere, 1998 ), these fi gures suggest that at least 60 % of SVPs are confi ned indefi nitely even though most would not have reoffended if released.…”
Section: Civil Commitmentmentioning
confidence: 91%
“…Even though evidence suggests that evaluators are quite adept at selecting only the highest risk offenders for civil commitment (Levenson, 2004 ;Mercado, Jeglic, Markus, Hanson, & Levenson, 2013 ), risk level alone is not suffi cient to identify those who ultimately will or will not recidivate. Overall, between 10 and 40 % of civilly committed SVPs can be expected to commit further sex offenses should they be released (Duwe, 2014 ;Milloy, 2003 ;Neller & Petris, 2013 ). While higher than the average rate of recidivism among non-SVP sex offenders (Hanson & Bussiere, 1998 ), these fi gures suggest that at least 60 % of SVPs are confi ned indefi nitely even though most would not have reoffended if released.…”
Section: Civil Commitmentmentioning
confidence: 91%
“…At the time of their 2009 study, Boccaccini and colleagues reported that no one classified as an SVP in the Texas outpatient SVP program had recidivated with a sexually violent offense, though some had been returned to prison for other reasons. Neller and Petris (2013), who attempted to model the likely recidivism rates of those committed SVPs using data on published recidivism rates and screening procedures for SVP commitment, speculate that as many as 60% of SVPs would have recidivated had they been released after their incarceration instead of committed.…”
Section: Outcomes Post-svp Commitmentmentioning
confidence: 99%
“…This is problematic, as research could validate the use of the legislation and evaluate the belief that the community is at risk. Among the studies on dangerous offenders, Neller and Petris (2013) used an estimation model to consider risk level of offenders likely to be classified as sexually violent predators (United States). From a population of 20,000 sex offenders, 740 persons were assumed to be committed under the sexually violent predator (SVP) law.…”
Section: Dangerous Sex Offenders and Recidivismmentioning
confidence: 99%